The Susceptibility to Mental Health Problems in the Future as a Serious Effect of Bullying on Adolescent: A Systematic Review - Ferry Diana Karmilasari; Indah Winarni; Heni Dwi Windarwati (International Journal of Science and Society, 2020)
Bullying was a type of action which performed repeatedly, from time to time which involved particular group or individual who had more power than the victim. This systematic review was aimed to identify the impacts of bullying to the mental health of adolescent. This systematic review was initiated from identifying scientific articles that have been published between 2015-2019 on five databases as PubMed, Clinical Key, Science Direct, ProQuest, and Springer Link. The search involved use of terms as effects, bullying, adolescent and mental health. Overall, from the result of searching, this research collected 26 articles which fitted to the inclusion criteria. The result of 26 articles were overall in quantitative research design. The long-term impact of bullying for the victim was a problem of mental health. The mental health problem which found on the victim of bullying as stress, depression and anxiety, idea of suicide, low self-esteem, withdrawal from social contact, loneliness and decrease of self-confidence. The findings showed that bullying could affect a long-term effect since the adolescent up to adult period.